High-throughput organ-on-a-chip systems: Current status and remaining challenges. (June 2018) - Probst, Christopher; Schneider, Stefan; Loskill, Peter
Abstract: Organ-on-a-chip (OoC) systems might be the disruptive technology pharmaceutical industry has been looking for to tackle their ever-increasing R&D costs. First endeavors are well underway to transfer this technology, which was until now used solely in academic settings, to industry. The high hopes of the OoC technology stem inter alia from its potential to merge strengths of animal models and cell culture, i.e., high physiological relevance and high throughput capacity. However, although the predictive value and physiological character of various OoC systems have been highlighted in numerous studies, the applicability for medium or even high-throughput screenings (HTS) has not been demonstrated yet. Adaptations such as massive parallelization and automation are among the biggest challenges in attempts to meet industrial benchmarks of HTS. In this review, we briefly introduce the demands of modern-day HTS in drug discovery and development, review the status-quo of parallelized OoC systems, and discuss the current limitation and remaining challenges that need to be overcome to increase the throughput of OoC experiments. Graphical abstract: Highlights: Demands of HTS. Parallelization efforts for OoC systems. Throughput limitations of OoC systems.